Analisis Pengaruh Pressure, Opportunity, Rationalization, Capability & Arrogance Terhadap Perilaku Kecurangan Akademik Pada Mahasiswa Jurusan Akuntansi Politeknik Negeri Padang - Amanda Anindya; Zalida Afni; Irda Rosita (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2023)
ABSTRACT This study aims to analyze the pressure, opportunity, rationalization, capability & arrogance of academic cheating behavior in students of the Accounting Department of the Padang State Polytechnic using fraud pentagon theory. This research uses quantitative methods. The data used are primary data obtained through questionnaires. The population of this study is active students of the Accounting Department of the Padang State Polytechnic (Regular and Non-Regular) odd semester in 2021/2022. The sample in this study was 248 students. The Method used in this study was purposive sampling using a multiple linear regression model. The results of this study simultaneously show that pentagon fraud theory affects academic cheating behavior. It partially shows that pressure, opportunity, rationalization, capability affect academic cheating behavior. In contrast, arrogance has no effect on academic cheating behavior.